(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
According to three years of research, the influence of mineral fertilizers and growth regulators under different sowing methods on the productivity of spring camelina varieties has been established. Problem statement. Increasing the yield of spring camelina requires the use of modern cultivation technologies, which are primarily based on the introduction of high-yielding varieties and the scientifically grounded application of mineral fertilizers and growth regulators. An additional important element of advanced technologies is the optimal spatial arrangement of plants in the crop stand, determined by row spacing.The aim of the research was to determine the specific features of productivity formation in spring camelina under the influence of mineral fertilizers, plant growth regulators, and sowing methods in the conditions of the Southern Steppe of Ukraine. Research methods. The study was conducted in 2023–2025 at the experimental field of the Institute of Oilseed Crops in the Zaporizhzhia district of Zaporizhzhia region. To address the research objectives, a four-factor field experiment was carried out. Factor A – row spacing (2 variants). Factor B – application of mineral fertilizers (4 variants). Factor C – variety (2 variants). Factor D – application of growth regulators (4 variants). The total number of experimental variants was 64. Replication was threefold. The establishment of the experiment, accounting, measurements, and accompanying observations were conducted according to standard field experiment methodologies. Research results. The number of seeds per plant in spring camelina was higher when sown with 70-cm row spacing in both varieties. Under the influence of mineral fertilizers and growth regulators, this indicator increased by: 1–20 and 1–18 seeds, respectively, for the variety Prestyzh; and by 1–37 and 1–32 seeds for the variety Slavutych.The seed weight per plant of spring camelina, depending on the variant of mineral fertilizer and growth regulator application, was higher under 70-cm row spacing by 0.04–0.06 g in the variety Prestyzh and by 0.06–0.08 g in the variety Slavutych. Under the influence of mineral fertilizers and growth regulators, seed weight per plant increased by 0.01–0.07 g and 0.01–0.04 g, respectively, in both varieties.The 1000-seed weight of spring camelina in the varieties Prestyzh and Slavutych was higher by 0.03–0.08 g and 0.02–0.05 g, respectively, under the wide-row sowing method. Under the influence of mineral fertilizers, the 1000-seed weight increased by 0.02–0.14 g in Prestyzh and by 0.01–0.10 g in Slavutych. Under the influence of growth regulators, the 1000-seed weight increased, depending on the nutrient background and sowing method, by 0.01–0.04 g in Prestyzh and by 0.01–0.03 g in Slavutych. Conclusions. The highest yield of spring camelina was obtained for the varieties Prestyzh – 1.32 t/ha and Slavutych – 1.40 t/ha when sown with 15-cm row spacing, combined with the application of mineral fertilizers at a rate of N40P40К40 and spraying the crop with the growth regulator Rost-koncentrat at the rosette stage. The yield increase amounted to 0.02–0.21 t/ha from the use of mineral fertilizers and 0.02–0.11 t/ha from the application of growth regulators.